Solvent‐Polarity‐Engineered Controllable Synthesis of Highly Fluorescent Cesium Lead Halide Perovskite Quantum Dots and Their Use in White Light‐Emitting Diodes. (18th October 2016) - Li, Guopeng; Wang, Hui; Zhang, Ting; Mi, Longfei; Zhang, Yugang; Zhang, Zhongping; Zhang, Wenjun; Jiang, Yang
Abstract : Cesium lead halide quantum dots (QDs) have tunable photoluminescence that is capable of covering the entire visible spectrum and have high quantum yields, which make them a new fluorescent materials for various applications. Here, the synthesis of CsPbX3 (X = Cl, Br, I, or mixed Cl/Br and Br/I) QDs by direct ion reactions in ether solvents is reported, and for the first time the synergetic effects of solvent polarity and reaction temperature on the nucleation and growth of QDs are demonstrated. The use of solvent with a low polarity enables controlled growth of QDs, which facilitates the synthesis of high‐quality CsPbX3 QDs with broadly tunable luminescence, narrow emission width, and high quantum yield. A QD white LED (WLED) is demonstrated by coating the highly fluorescent green‐emissive CsPbBr3 QDs together with red phosphors on a blue InGaN chip, which presents excellent warm white light emission with a high rendering index of 93.2 and color temperature of 5447 K, suggesting the potential applications of highly fluorescent cesium lead halide perovskite QDs as an alternative color converter in the fabrication of WLEDs. Abstract : CsPbX3 quantum dots (QDs) have superior photophysics properties, including high quantum yield (up to 72%), wide color gamut (>NTSC standard), and narrow emission width (18–38 nm). The WLED based on CsPbBr3 QDs present excellent warm white light emission with a high rendering index of 93.2 and CIE coordinate of (0.3339, 0.3617).